Perancangan instalasi kabel 20 kV pada auxiliary transformer sebagai alternatif back feeding PLTGU Jawa 2 - Afrianda, Rio; Putra, Setianto Rama (Universitas Negeri Yogyakarta, 2023)
Dalam rangka mewujudkan program pemerintah 35000 MW dilakukan pembangunan Pusat Listrik Tenaga Gas dan Uap (PLTGU) Jawa 2, kapasitas daya sebesar 800 MW dengan sistem interkoneksi 500 kV yang terletak di daerah PLTGU Tanjung Priok Jakarta Utara. Pada PLTGU Jawa 2 dalam pelaksanannya terdapat beberapa tahapan sebelum dilakukan pengoperasian pembangkit seperti tahapan konstruksi dan pengujian/komisioning. Dalam pengujian peralatan, kebutuhan listrik menggunakan sumber daya listrik dari jaringan eksisting milik PT PLN atau disebut juga dengan back feeding. Salah satu alternatif back feeding PLTGU Jawa 2 adalah dengan menggunakan sumber daya listrik dari kubikel 20 kV GIS 150 kV Priok Timur Lama.Cara ini berpotensi mengalami keterlambatan apabila instalasi penyambungan kabel 20 kV yang menyuplai unit auxiliary transformer tidak dilakukan dengan benar. Kabel 20 kV yang terhubung dengan bushing unit Auxiliary Transformer akan mengalami stress cable jika nilai bending radius kabel dalam penyambungan kabel 20 kV ke bushing unit auxiliary transformer tidak diperhatikan. Dari kendala tersebut dapat dilakukan kajian mengenai perancangan instalasi penyambungan kabel 20 kV yang menyuplai unit Auxiliary Transformer. Selain itu, kajian mengenai penentuan jenis kabel 20 kV yang akan digunakan juga diperlukan agar sumber daya listrik dapat tersalurkan ke peralatan yang akan dilakukan pengujian secara optimal. Dengan dilakukan kajian tersebut pelaksanaan back feeding dapat berjalan sesuai jadwal yang telah ditentukan dan kendala saat pelaksanaan pengujian back feeding dapat diantisipasi sebelumnya.Kata kunci: back feeding, unit auxiliary transformer, kabel 20 kV Design of 20 kV cable installation on auxiliary transformer as an alternative back feeding for PLTGU Jawa 2Abstract: In order to actualize the 35,000 MW government program, the JAWA 2 Combined Cycle Power Plant (PLTGU) is built, with a power capacity of 800 MW and distributed trough a 500 kV interconnection system located in the PLTGU Tanjung Priok area, North Jakarta. This project have several stage before the operation such as planning, construction and testing/commissioning. In testing period, the electricity required for testing the equipment is supplied from the existing power grid or also known as back feeding. One of the alternatives for back feeding PLTGU Jawa 2 is to use electricity from the 20 kV GIS 150 kV cubicle of Priok Timur Lama, this method has the potential of delays if the installation of the 20 kV cable connection that supplies the Auxiliary Transformer unit is not carried out properly. The 20 kV cable connected to the Auxiliary Transformer bushing unit will experience cable stress if the bending radius of the cable in connecting the 20 kV cable to the Auxiliary Transformer bushing unit is not taken into account. From these constraints a study can be carried out on the installation design of the 20 kV cable connection that supplies the Auxiliary Transformer unit. moreover, a study to determine of the type of 20 kV cable is also necessary so that the power source can be optimally distributed to the equipment to be tested. With this study, the back feeding can proceed according to a predetermined schedule and any issue during the back feeding test can be anticipated beforehand. Keywords: back feeding, unit auxiliary transformer, 20 kV cable